Development and clinical application of a rapid and visual loop-mediated isothermal amplification test for tetM gene in Clostridioides difficile strains cultured from feces. (September 2022) - Lin, Minyi; Li, Zitong; Lin, Qianyun; Wang, Pu; Liu, Wei; Yuan, Jing; Hong, Zhongsi; Chen, Ye
Highlights: The rapid and accurate diagnosis of the tetM gene in Clostridioides difficile is important. We evaluated a loop-mediated isothermal amplification assay for detecting the tetM gene. We compared assay sensitivity and specificity with a polymerase chain reaction. The assay was visual and more rapid and confirmed the tetM gene in 300 clinical strains. Abstract: Objectives: In this study, we aimed to develop a rapid and visual loop-mediated isothermal amplification (LAMP) assay targeting the tetM gene in Clostridioides difficile strains cultured from feces. Methods: Primers were designed to recognize the tetM gene in C. difficile by LAMP, using turbidity and visual detection. The sensitivity and specificity of LAMP primers were determined. In addition, we conducted both LAMP and polymerase chain reaction (PCR) for the tcdA, tcdB, cdtA, cdtB, ermB, and tetM genes in 300 toxigenic C. difficile strains cultured from feces. Results: The target DNA was amplified and visualized within 60 minutes at a temperature of 62°C. A total of 26 bacterial strains were found negative for tetM, which manifested high specificity of the primers. The detection limit of LAMP was 36.1 pg/µl, which was 100-fold more sensitive than PCR. The positive rate of tetM in toxigenic C. difficile strains cultured from feces was 93.3% by both LAMP and PCR. The proportion of toxin types in those C. difficile strains was 95.7% for A+B+CDT−, 4% for A−B+CDT−, and 0.3% for A+B+CDT+, respectively. Conclusion: This is the first study examining the tetM gene by LAMP in C. difficile strains cultured from feces. Its high specificity, sensitivity, and visual detection make the new assay a powerful diagnostic tool for rapid testing.